Effect of pulmonary function on cardiorespiratory condition, mobility, and balance in people aged over 50 years: a cross-sectional study - Alegria, Valdirene Tenório Da Costa [UNESP]; Manzano, Roberta Munhoz; Ambrozin, Alexandre Ricardo Pepe [UNESP] (Universidade de São Paulo, 2025)
This study aimed to evaluate the effect of static pulmonary function variables on cardiorespiratory condition, mobility, and balance in people aged over 50 years, as well as the effect of mobility and balance on three stress tests in the same sample. This is a cross-sectional study. Pulmonary function evaluation was performed by spirometry, the incremental shuttle walking test (ISWT), the six minute walk test (6MWT), the stairs test (ST), the timed up and go test (TUGT), and the Berg balance scale (BBS). SigmaStat® was used for statistical analysis, and the variables were correlated using Pearson’s correlation test (p<0.05). The sample consisted of 46 people [37 women (80.5%) and nine men (19.5%)] with a mean age of 61.02±8.29 years. Results of the correlation of pulmonary function with stress, mobility, and balance and stress tests were correlated with spirometric variables. In the sample, people with lower time in TUGT and better balance conditions who had better lung function. The better the mobility, the better the results in the stress tests. TUGT results showed moderate correlation with ISWT (0.41) and actual 6MWT (−0.43). On the other hand, BBS scores showed moderate correlation with ISWT(%) ((−-0.45), real 6MWT (0.43), and actual (−0.59) and predicted ST (-0.45). We conclude that pulmonary function affects cardiorespiratory condition, mobility, and balance in people aged over 50 years.

El objetivo de este estudio fue evaluar el efecto de las variables estáticas de la función pulmonar sobre la respuesta cardiorrespiratoria, en la movilidad y en el equilibrio en personas mayores de 50 años. En la misma muestra, también se analizó el efecto de la movilidad y del equilibrio en tres pruebas de esfuerzo diferentes. El estudio es transversal. La función pulmonar se evaluó mediante espirometría, prueba de caminata de carga progresiva (ISWT), prueba de caminata de seis minutos (PC6M), prueba de escalera (TESc), prueba timed up and go (TUG) y escala de equilibrio de BERG (BERG). Para el análisis estadístico, se utilizó el software SigmaStat®, las variables se correlacionaron mediante el uso de la correlación de Pearson (p<0,05). La muestra estuvo compuesta por 46 personas, de las cuales 37 (80,5%) eran mujeres; y 9 (19,5%), hombres, con una edad media de 61,02±8,29 años. Los resultados de la correlación de la función pulmonar con las pruebas de esfuerzo, movilidad y equilibrio mostraron correlación con las variables espirométricas. En la muestra, las personas con el menor tiempo en TUG y mejores condiciones de equilibrio tuvieron la mejor función pulmonar. Cuanto mejor sea la movilidad, mejores serán los resultados en las pruebas de esfuerzo. Los resultados de TUG mostraron una correlación moderada con ISWT (0,41) y PC6M real (-0,43). La puntuación de BERG presentó una correlación moderada con ISWT(%) (-0,45), PC6M real (0,43) y tTEsc [real (-0,59) y predicho (-0,45)]. Se concluye que la función pulmonar tiene un efecto sobre la condición y la respuesta cardiorrespiratoria, la movilidad y el equilibrio en personas mayores de 50 años.
Efecto de la función pulmonar en la condición y respuesta cardiorrespiratoria, movilidad y equilibrio en personas mayores de 50 años: un estudio transversal
Keywords: Aging; Pulmonary Function; Mobility; Balance